StarCraft Legacy of the Real-Time Strategy - Dor, Simon (Landmark Video Games, 2024)
StarCraft (Blizzard Entertainment, 1998) is a real-time strategy video game, placing the player in command of three extraterrestrial races fighting against each other for strategic control of resources, terrain, and power. Simon Dor examines the game's unanticipated effect by delving into the history of the game and the two core competencies it encouraged: decoding and foreseeing. Although StarCraft was not designed as an e-sport, its role in developing foreseeing skills helped give rise to one of the earliest e-sport communities in South Korea. Apart from the game's clear landmark status, StarCraft offers a unique insight into changes in gaming culture and, more broadly, the marketability and profit of previously niche areas of interest. The book places StarCraft in the history of real-time strategy games in the 1990s-Dune II, Command & Conquer, Age of Empires-in terms of visual style, narrative tropes, and control. It shows how design decisions, technological infrastructures, and a strong contribution from its gaming community through Battle.net and its campaign editor were necessary conditions for the flexibility it needed to grow its success. In exploring the fanatic clusters of competitive players who formed the first tournaments and professionalized gaming, StarCraft shows that the game was key to the transition towards foreseeing play and essential to competitive gaming and e-sports.